FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA DI DESA MELILINGKECAMATAN KERAMBITAN KABUPATEN TABANAN - Wardani, Made Kusuma; Sudarsani, Ni Putu; Weda Subawa, I Gede Putu; Terimajaya, I Wayan; Kusuma, Bagus Arya (Universitas Mahendradatta, 2025)
ABSTRACT Street vendors (PKL) are informal sector businesses in the form of trading businesses which are sometimes also producers. There are those who stay in certain locations, there are those who move from one place to another (using poles, pushcarts) selling food, drinks and other consumer goods at retail. Street vendors, generally with small capital, are sometimes only a tool for capital owners to get just a commission as a reward or their hard work. The aim of this research is to determine the partial or simultaneous influence of business capital, working hours and sales on sales of street vendors in Meliling Village, Kerambitan District, Tabanan Regency. The analytical tool used in this research is multiple linear regression with hypothesis testing, namely for partial using the t test and for simultaneous using the F test and the samples used were 30 samples. Research results 1) Business capital has a partial positive and real effect on the income of street vendors in Meliling Village, Kerambitan District, Tabanan Regency. 2) Working hours have a partial positive and real effect on the income of street vendors in Meliling Village, Kerambitan District, Tabanan Regency. 3) Sales have a partial positive and real effect on the income of street vendors in Meliling Village, Kerambitan District, Tabanan Regency. 4) Capital, working hours and sales have a significant simultaneous effect on the income of street vendors in Meliling Village, Kerambitan District, Tabanan Regency. Keywords: capital, working hours, sales and income